Fibroblast growth factor 18 regulates steroidogenesis in fetal bovine ovarian tissue in vitro - Silva, Rubia Bueno da [UNESP]; Yang, Ming Y.; Caixeta, E. S. [UNESP]; Castilho, Anthony C. [UNESP]; Amorim, R. L. [UNESP]; Price, C. A.; Fortune, J. E.; Buratini, J. [UNESP] (Wiley-Blackwell, 2019)
In cattle and other species, the fetal ovary is steroidogenically active before follicular development commences, and there is evidence that estradiol and progesterone inhibit follicle formation and activation. Estradiol levels decline sharply around the time of follicle formation. In the present study, we hypothesized that FGF10 and FGF18, which inhibit estradiol secretion from granulosa cells of antral follicles, also regulate fetal ovarian steroid production. Fetuses were collected at local abattoirs, and age determined by crown-rump length measurements. Real-time polymerase chain reaction assays with RNA extracted from whole ovaries revealed that the abundance of CYP19A1 messenger RNA (mRNA) decreased from 60 to 90 days of gestation, which is consistent with the decline in estradiol secretion previously observed. Immunohistochemistry revealed the presence of FGF18 in ovigerous cords in early gestation and in oocytes later in fetal age (>= 150 days). The abundance of FGF18 mRNA increased after Day 90 gestation. Addition of recombinant FGF18 to fetal ovarian pieces inhibited estradiol and progesterone secretion in vitro, whereas FGF10 was without effect. Consistent with these results, FGF18 decreased levels of mRNA for CYP19A1 and CYP11A1 in ovarian pieces in vitro. These data suggest that FGF18 may be an intraovarian factor that regulates steroidogenesis in fetal ovaries.
Keywords: cattle; fibroblast growth factor 10; fibroblast growth factor 18; ovarian follicle; ovary; steroids